Long term benefit of a targeted diabetes education program: the KK Chini experience. - Kamaruzaman, Nor Azam; Pasi, Hafizah; Bakar, Bustamanizan; Z, Asyikin (Academy of Family Physicians of Malaysia (AFPM), 2021)
An effective diabetes education may empower the patient in reinforcing self-care and a healthy lifestyle. We aim to evaluate the one-year outcome of an education program on a targeted group of diabetic patients at a primary health clinic. The study showed that before the program, mean HbA1c level was 9.8% and a significant reduction in mean HbA1c of 1.2% was shown one year after the program. For the same duration of time, there were no new incidence of co-morbidities or diabetic complications and no significant changes in fasting blood glucose, serum creatinine and body weight was found among these patients. In term of treatment, the total dose/day of diabetic medications also showed no significant difference. In conclusion, diabetic education program which is structured, multi-disciplinary and targeted on poorly controlled patients was shown to be beneficial in a one-year outcome without the need for intensification of therapy.